Insertion and use of multicriteria methods for neutrosophic judicial evaluation - Roberto Carlos Jiménez Martinez; María José Calderón Velásquez; Manuel Augusto Suarez Albiñol; Yusleidy Marlie Gordo Gómez (Neutrosophic Sets and Systems)
This study addresses the growing need to integrate multicriteria methods into judicial evaluation, specifically through a neutrosophic approach, to improve the accuracy and reliability of legal decision-making. Today, the judicial system faces critical challenges related to the interpretation of evidence, the consideration of multiple factors, and the uncertainty inherent in complex cases. Although various approaches have been used in judicial evaluation, few effectively address the ambiguity and indeterminacy present in the opinions of judges and experts, leading to fragmented or biased analysis. This study seeks to close that gap by applying neutrosophic multicriteria methods, which allow for a more balanced and comprehensive evaluation, incorporating all dimensions of the judicial process, from evidence to contextual factors. The methodological approach adopted is based on the use of neutrosophic multicriteria tools, which allow for the integration and analysis of various criteria through a flexible and robust framework. The results obtained reveal that this method not only improves the accuracy of judicial assessments but also provides a clearer view of the uncertainty associated with legal decisions. The main theoretical implications of this study lie in the possibility of applying a neutrosophic framework to judicial assessment, providing a tool capable of capturing the complexity of disputed cases. On a practical level, the findings are crucial for the development of judicial decision support systems, suggesting that the implementation of this approach could contribute to greater objectivity and consistency in judicial decisions, as well as to an improvement in the transparency of the judicial process.